Development of a pure sinusoidal single phase inverter / Mohamad Habib Ismail and Nazhirah Adam - Ismail, Mohamad Habib; Adam, Nazhirah (2005)
Dc-to-ac converters are known as inverter. The function of an inverter is to change a dc input voltage into a symmetric ac output voltage of desired magnitude and frequency. A variable output voltage can be obtained by varying the input dc voltage and maintaining the gain of the inverter constant. In this project, a pure sinusoidal single phase inverter was designed. This inverter takes 12 volt d.c and steps it up to 240 volt a.c. The output voltage waveform should be sinusoidal. However, the waveform of this inverter are nonsinusoidal and contain certain harmonics. We also used centre tapped transformer that step up the voltage to 240V ac. In the modifying process, we included a fuse at the output of the voltage. So it be more safety. We also included a bulb at the output that will easier to us to make sure there is no damage in our circuit.